Laku pandai’s program and deposit funds: study at bank of bri sharia - Al Arif, M. Nur Rianto; Firmansyah, Firmansyah (Jurnal Ekonomi, 2018)
Laku Pandai’s program is one of the policies that implemented by the financial service authority (OJK) to expand the banking service to the people. One of the Islamic banks that had implemented the program is Bank of BRI Sharia. This research is going to examine the effectiveness of Laku Pandai’s program to deposit funds in Bank of BRI Sharia. This study using regression with the dummy variable. The result shows that there is a difference between pre and post-Laku Pandai’s program in Bank of BRI Sharia. This result implies that the Laku Pandai’s implementation had an impact on increasing deposit funds in Bank of BRI Sharia. So, it is recommended to add more Islamic banks that implemented the Laku Pandai’s program